Les avocats du Mouvement d'Action Judiciaire dans les années 1970, entre remise en cause du modèle professionnel et pratiques du droit originales - Jean-Philippe Tonneau (Criminocorpus)
The article is interested in the Mouvement d'Action Judiciaire. Created in 1968, the organization wishes to include « workers of rights » : Lawyers, magistrates but also factory inspectors, educators, etc., and gives itself three objectives : « Make rights penetrate into the places where they are excluded; social struggles (legal or illegal); and fights inside the legal system ». Having redrawn the history of the MAJ, the article tightens then the focal on the lawyers who are members there (who are they and what are their professional practices?), then the article is interested in the future of the lawyers, when the organization disappeared in 1978.